2015
DOI: 10.1093/mnras/stv845
|View full text |Cite
|
Sign up to set email alerts
|

Mascon gravitation model using a shaped polyhedral source

Abstract: In the last two decades, new computational tools have been developed in order to aid space missions to orbit around irregular small bodies. One of the techniques consists in rebuilding their shape in tetrahedral polyhedron. This method is well suited to determine the shape and estimate certain physical features of asteroids. However, a large computational effort is necessary depending on the quantity of triangular faces chosen. Another method is based on a representation of the central body in terms of mascons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 13 publications
2
34
0
1
Order By: Relevance
“…In this work, we modeled the gravity field of the asteroid (101955) Bennu using the new approach of mascon gravitation, developed by Chanut et al (2015a), where the Mascon gravity framework (Geissler et al 1997) was applied using the shaped polyhedral source (Werner 1994). We tested this model analysing the equilibria near (101955) Bennu when the solar radiation pressure is not accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, we modeled the gravity field of the asteroid (101955) Bennu using the new approach of mascon gravitation, developed by Chanut et al (2015a), where the Mascon gravity framework (Geissler et al 1997) was applied using the shaped polyhedral source (Werner 1994). We tested this model analysing the equilibria near (101955) Bennu when the solar radiation pressure is not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently Wang et al (2016) have shown that within the limits of density and rotation defined by Chesley et al (2014), the centre points can become linearly stable by changing the topological structure from case 5 to case 1 ). In Aljbaae et al (2017), we presented the corrected form of the second order derivatives of Chanut et al (2015a). We solved the linearized state equations in the neighbourhood of the equilibrium points ), and we show the unnormalized eigenvalues and their stability type in Table 5.…”
Section: Zero Velocity Curves and Equilibriamentioning
confidence: 99%
See 3 more Smart Citations